1989
DOI: 10.1002/1098-108x(198911)8:6<607::aid-eat2260080602>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Ego functioning in eating disorders: Description and relation to diagnostic classification

Abstract: A working assumption for many clinicians is that differences in personality functioning among eating‐disordered patients are crucial for treatment planning and prognosis. However, the empirical documentation is scarce. The present study used analyses of 13 objectively rated ego functions in a sample of 48 eating‐disordered patients to try to establish a firmer empirical basis in the area. The variation in ego functioning was great, and a cluster analysis identified four clusters. These were tentatively named “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…There is evidence that these disorders can also occur in a relatively structured psyche then re ecting a neurotic internal con ict (Thiel & Schüßler, 1995). An investigation of the level of personality organization in eating disordered subjects according to Kernberg revealed that about 30% have a high (neurotic) level of structure, which is in concordance with the above cited studies (Norring, Sohlberg, Rosmark, Humble, Holmgren & Nordquist, 1989;Thiel & Schü ßler 1995). As each aetiological model of eating disorders developed so far, the self-psychological approach helps us to understand (only) a part of the aetiology and a number of patients, in particular those with high levels of self-regulatory disturbance (Goodsitt, 1997;Treasure, 1998).…”
supporting
confidence: 85%
“…There is evidence that these disorders can also occur in a relatively structured psyche then re ecting a neurotic internal con ict (Thiel & Schüßler, 1995). An investigation of the level of personality organization in eating disordered subjects according to Kernberg revealed that about 30% have a high (neurotic) level of structure, which is in concordance with the above cited studies (Norring, Sohlberg, Rosmark, Humble, Holmgren & Nordquist, 1989;Thiel & Schü ßler 1995). As each aetiological model of eating disorders developed so far, the self-psychological approach helps us to understand (only) a part of the aetiology and a number of patients, in particular those with high levels of self-regulatory disturbance (Goodsitt, 1997;Treasure, 1998).…”
supporting
confidence: 85%
“…It suggests some restricteribinger differences (e.g., restricters being more obsessional), but not a dichotomy. Given such conflicting findings, and reports that fail to support the "dichotomy" concept altogether (Norring et al, 1989), factors that might make the "restricted binger dichotomy" an "elusive" phenomenon must be considered.…”
Section: Scu Ss Ionmentioning
confidence: 99%
“…For example, a second study based on DSM-III-R criteria reports comparable distributions of diagnoses from "dramatic-erratic" and "anxious-fearful" PD clusters, among patients divided into restricter and binger groups (Gartner et al, 1989). Another, using cluster analysis techniques on multiple measures of ego functioning, identifies "higher neurotic," "lower neurotic," "borderline," and "borderline-psychotic" organizations in restricters and bingers alike (Norring et al, 1989). Our own studies on personality and defensive organization also fail to reveal clear-cut restricteribinger differences (Steiger, Van der Feen, Goldstein, & Leichner, 1989;Steiger, Goldstein, Mongrain, & Van der Feen, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Interrater reliability as judged from the audiotaped interviews was highly satisfactory (average r = .77; cf. Norring et al, 1989). Overall mental health, using the Global Assessment Scale (GAS) (Endicott, Spitzer, Fleiss, & Cohen, 1976), was rated from this interview also.…”
Section: Procedures and Evaluation At Presentationmentioning
confidence: 99%
“…All patients had a clinically significant preoccupation with weightbody shape (cf. Norring et al, 1989). Insistence on the presence of this preoccupation ensures that the ED NOS diagnosis is given only to patients whose disturbance is of obvious clinical proportions.…”
Section: Patientsmentioning
confidence: 99%